UTILIZATION OF E-COMMERCE AS A LEARNING MEDIA FOR DIGITAL MARKETING AND SOCIAL MEDIA FOR ENTREPRENEURSHIP STUDENTS - Mona Amelia; Jimi Ronald; Vivina Eprillison; Stevani Stevani; Jefri Irwanto (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2025)
Digital transformation has changed the way business people market their products through E-Commerce and social media. This condition requires the world of education, especially entrepreneurship study programs, to equip students with applicable digital marketing skills. E-Commerce not only functions as a transaction medium, but also as a means of learning digital entrepreneurship practices that integrate online store management, promotional strategy creation, and direct interaction with consumers through social media. This study aims to analyze the effect of the use of E-Commerce and the use of social media on students' understanding of entrepreneurship in the Digital Marketing and Social Media course. The research method uses a quantitative approach with the Partial Least Square (PLS) technique with 35 respondents from the Entrepreneurship study program, Faculty of Economics and Business, Universitas PGRI Sumatera Barat . The results of data processing show that all indicators are valid and reliable with Outer Loading values above 0.70, AVE above 0.50, and Composite Reliability exceeding 0.70. Path Coefficient shows a significant influence of the use of E-Commerce (β = 0.52; p = 0.001) and social media (β = 0.47; p = 0.004) on students' understanding of digital marketing. This study is expected to be a reference for universities in designing an entrepreneurship curriculum based on digital practices that are in line with the development of the digital economy. The integration of E-Commerce and social media as learning media is believed to be able to produce young entrepreneurs who are adaptive, creative, and ready to face the challenges of the digital market.